A qualitative study of medical students' perceptions of resident feedback. Issue 10 (9th June 2022) - Wong, Shannon N.; Luo, Cong (John); MacDonald, Graham; Hatala, Rose
Abstract: Context: Residents play a pivotal role in medical students' clinical education. From a feedback lens, the near‐peer relationship between student and resident holds the potential to foster an educational alliance that could influence learning. We undertook the current qualitative study to explore medical students' perceptions of feedback experiences with residents, addressing when, how and why (and conversely when not and why not) resident feedback plays a role in their clinical education. Methods: Our methodology was qualitative interpretive description, informed by phenomenology. We conducted 24 semi‐structured interviews with third and fourth year medical students at one institution. The interviews aimed to foster rich discussion about students' feedback experiences with residents during clinical rotations. Data collection and analysis proceeded iteratively. Initial interviews were independently open‐coded by three investigators and then collaboratively refined. Codes were applied to subsequent interviews, and new codes were developed. During the final stages of analysis, we organised our themes by drawing on a sociocultural perspective to examine students' perceptions of relationship‐building with residents and when and how this influenced feedback and learning. Results: From the students' perspectives, when residents contributed to building interpersonal relationships with students, this in turn influenced students' receptivity to both encouraging and constructive feedback conversations. In the context of resident–student relationships that were perceived as supportive, resident feedback influenced how students approached learning and working in the clinical environment, as well as students' visions of their future selves. In unsupportive relationships, students were less inclined to engage in feedback with residents and students noted resident behaviours that they wanted to avoid in themselves. Conclusion: Residents are uniquely positioned to create a strong educational alliance with students in which feedback conversations can flourish. Focusing educational efforts on resident feedback conversations has the potential to significantly impact the feedback culture of our clinical environments. Abstract : Wong et al. demonstrate that residents are uniquely positioned to create a strong educational alliance with students in which feedback conversations can flourish.